Vincas Mykolaitis-Putinas’ Literary History: Narrative’s Methodological Singularities - Dragenytė, Ramutė (Colloquia, 2014)
The Lithuanian classic Vincas Mykolaitis-Putinas’ literary history, Naujoji lietuvių literatūra (The New Lithuanian Literature; Volume 1 published 1936; Volume 2, 2009) was the first conceptual, academic history of Lithuanian literature. In this metanarrative account, Mykolaitis-Putinas sought to methodologically describe different authors in terms of each one’s national and aesthetic consciousness. This national historiographic narrative was made possible by the grand national narrative that shaped the Lithuanian literary canon: the development of a national Lithuanian literature and the identification of its most important texts, genres, directions, and authors. Naturally, this grand narrative dictated Mykolaitis-Putinas’ writing methodology, as though the author were hostage to the cultural-historical school of positivism, forced to provide cultural contexts, present dry writers’ biographies, and look for causal connections. His categorization of literary historical content was determined by the quest for a national program characteristic of Romantic literary history – idealized subjects, rather than literary facts. On the other hand, anti-positivist aesthetics (drawn from Wilhelm Dilthey, Benedetto Croce, Maurice de Munnynck, Oscar Walzer, and others) also had considerable influence on his interpretation of the works. Although Mykolaitis-Putinas sought to assess the texts historically, from the perspective of the time he was examining, his own aesthetic views led him to have a critical relationship with literary history as a whole. Each author was critiqued – in terms of content, but even more so in terms of form.The literary history under discussion is a synthesis of two historiographic models: following Romanticism’s model of literary history, it tracesthe nation’s spiritual develoment; following historicist positivism, it seeks to understand different periods, the development of genres and directions, and explores causal connections and cultural contexts. This interpretive model presupposed an aesthetic understanding and the search for a “selfcontained literature”. Mykolaitis-Putinas’ history is a biographical-psychological, aesthetic, and – most importantly – a critical analysis of Lithuanian literature.
Keywords: Vincas Mykolaitis‑Putinas; literary history; grand narrative; national consciousness; positivist historiography; hermeneutic historiography